Examining the relationship between principals' leadership style and their level of emotional intelligence / Lau Ngee Kiong and Sueb Ibrahim - Lau, Ngee Kiong; Ibrahim, Sueb (Akademi Pengajian Bahasa, 2012)
As the context of leadership is changing, to lead effectively will be critical to the longterm success of organizations. Therefore, school principals will need to combine several leadership qualities in order to succeed. School principals have to develop their rational in establishing which leadership style will result to high performance outcomes and leadership effectiveness. Thus, the nature of the leader's emotional connectedness to others is apparently in the growing interest in numerous studies on the effect of emotional intelligence on leadership. Moreover, at present, there seems to be increasing attention being given to organizational life and leadership and general agreement about the need to incorporate the role of emotion into research on educational leaders. To be effective school leaders in pursuit of effective leadership, there should be a significant link between principals' leadership style and their level of emotional intelligence and how this link can be a driving force that can bring an impact on their leadership effectiveness. Moreover, to build the leadership capacity necessary for effective leadership, school principals will not only need to possess effective leadership style, but also well-developed social and emotional skills. A high IQ can do much to resolve leadership challenges; however, without allowing the heart to intervene, one is at disadvantage in being an effective leader (Chemise & Adler, 2000; Goleman, 1995; Ryback, 1998). Therefore, utilizing these connections, this study seeks to identify the connection of principal's leadership style and emotional intelligence. The main aim of this study was to identify the relationship between principals' leadership style and their level of emotional intelligence. Although research on emotional intelligence and effective leadership is growing, there still remains a gap on the relationships that exist between emotional intelligence and leadership. This study saught